EFISIENSI PENGGUNAAN RADIASI MATAHARI DAN PARTISI BAHAN KERING BIBIT KELAPA SAWIT PADA BERBAGAI DOSIS PUPUK KALIUM DAN MAGNESIUM - Adinda Nurul Huda Manurung; Suwarto Suwarto; Sudirman Yahya; Budi Nugroho (Jurnal Agrotek Tropika, 2024)
Optimization of radiation and dry matter partitioning is carried out to increase oil palm productivity. This study aimed to study the effect of various doses of K and Mg fertilization on the radiation use efficiency (RUE) and carbohydrate partitioning of oil palm seedlings in the main nursery. The study was conducted at the Leuwikopo IPB experimental garden, Bogor, from April 2021 to January 2022. The study used a non-factorial Randomized Block Design with five replications of 2 separate experiments. Experiment I consisted of five levels of K fertilization treatment (0%, 50%, 100%, 150%, and 200%). Experiment II consisted of five levels of Mg fertilization treatment (0%, 50%, 100%, 150%, and 200%). Differences in K and Mg fertilizer doses caused variations in dry weight, Leaf area index (LAI), RUE, and partitioning of oil palm seedlings. The best RUE value of oil palm seedlings during the main nursery was obtained in the K2 treatment (100% K dose), 1.24 g MJ-1, and M2 (100% Mg dose), 0.94 g MJ-1. Fluctuations in the partition of dry matter of roots, petioles, and leaves due to differences in K fertilization doses were 0.08-0.29%, 0.39-0.42%, and 0.31-0.50%. Fluctuations in the partition of dry matter of roots, petioles, and leaves due to differences in Mg fertilization doses were 0.04-0.16%, 0.40-0.50%, and 0.34-0.56%.